2017
DOI: 10.1016/j.synbio.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and antioxidant properties from mushrooms

Abstract: Preventive medicine and food industry have shown an increased interest in the development of natural antioxidants, since those most commonly used synthetic antioxidants may have restricted use in food. This could explain why there is currently much research on the antioxidant properties from natural products such as mushrooms. Many mushrooms have been reported to possess antioxidant properties, which enable them to neutralize free radicals. The oxygen molecule is a free radical, which lead to the generation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
113
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(127 citation statements)
references
References 71 publications
4
113
0
10
Order By: Relevance
“…However, at high concentration, ROS results in oxidative damage of macro-molecules, which is extremely harmful to the organism. Studies have demonstrated the implication of ROS in the development and progression of several life threatening diseases including diabetes, neurodegenerative, cancer, atherosclerosis, and cardiovascular diseases [30,31]. Antioxidants are molecules that avert the harmful effects of ROS by inhibiting the oxidation of oxidizable substrates.…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
“…However, at high concentration, ROS results in oxidative damage of macro-molecules, which is extremely harmful to the organism. Studies have demonstrated the implication of ROS in the development and progression of several life threatening diseases including diabetes, neurodegenerative, cancer, atherosclerosis, and cardiovascular diseases [30,31]. Antioxidants are molecules that avert the harmful effects of ROS by inhibiting the oxidation of oxidizable substrates.…”
Section: In Vitro Antioxidant Activitymentioning
confidence: 99%
“…Homopolysaccharides, particularly glucans, are indeed the most responsible for mushrooms biological activities [26], and recent studies also revealed the therapeutic properties of mushrooms heteropolysaccharides [27]. Mushrooms are also rich in bioactive compounds [28][29][30], thus possessing radical scavenging activity and exerting antibacterial effects [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the incorporation of plant-based products into animal origin foods has been highlighted because of their nutritional profile (e.g., no cholesterol, low fat ingredients) (Reis et al 2017). In addition to plants, mushrooms have also emerged as raw materials to be studied and applied in food industries (Sánchez, 2017).…”
Section: Introductionmentioning
confidence: 99%